Handbook of physical vapor deposition (PVD) processing film formation, adhesion, surface preparation and contamination control - Mattox, D. M. (Noyes Publications, 1998)
Covers aspects of the Physical Vapor Deposition process technology from characterizing and preparing the substrate material, through deposition processing and film characterization, to post-deposition processing. Includes subjects such as substrate characterization, adhesion, cleaning, and processing. Also covers the more widely discussed subjects of vacuum technology and the fundamentals of individual deposition processes.
Keywords: Vapor-plating -- Handbooks, manuals, etc.; elektronické knihy; electronic books